SEMILIGNEUOS STAKING AND COMPARISON OF SECONDARY METABOLITS IN Mikania glomerata SPRENGEL AND Mikania laevigata SCHULTZ BIP EX BAKER - LIMA, Narumi Pereira (Scientia Agraria, 2002)
Seeking to the obtein technical subsides to the production in commercial scale of the guaco, the general objective of the presente study was optimizing the propagation process through cuttings of the guaco, and the specific objectives were to analyze phytochemically the possible use of the Mikania laevigata as succedaneous of Mikania glomerata, to determinate the leaf area, the time of immersion in water, the substratum and the irrigation system indicated in the cuttings of guaco and to comparate the yielding of the two species in the field. Three cuttings experiments were accomplished, to verify the effect of the leaf area, the time of immersion of the base of the cuttings in water and of the interaction substratum x irrigation system in the cutting of the two guaco species. In the first experiment, the following leaves area were tested: 0, 5, 25, 50 and 100 cm2. In the second experiment was tested the following substratum: carbonized rice seed coat, sands and soil, each one under two different irrigation systems (nebulization or manual irrigation). In the third experiment, it was tested 0, 3, 6, 12 and 24 hours of immersion in water. For all the experiments, it was used cuttings with 12 cm of length, diameter of 0,8 to 1,0 cm, taking from the medium part of the branches; the experimental design is a randomized complet blokm with four replication and twenty cutting each plot. The evaluation was made, respectively, 75, 60 and 90 days after the installation of the experiments. The increase of the leaf area caused increase in the root system and a decrease in the mortality of the two species, fitting to stand out that M. glomerata presented smaller development of the radicial system than M. laevigata. With relatioship to the interaction substratum x irrigation system, was verified that, in general, as for M. glomerata as for M. laevigata, the substratum carbonizes rice seed coat under manual irrigation presented the best results. The time of immersion of the base of the cuttings in water didnt affect significantly, for both species, none of the variables. In the study seeking to compare the yielding of two species, plantlets were planted in the Fazenda Experimental do Cangüiri of the Universidade Federal do Paraná (UFPR), in 11/25/1998, in space holes of 1,0 m in the line and 2,0 m between lines, with conduction in spalier with threads to 0,8, 1,2 and 1,6 m of heigth. The experimental design was a randomized complet books, with three replication and three plants each plot. The occurence of a strong frost in the winter of 1999 caused the death of the plants of M. glomerata. The yielding of M. laevigata, evaluated 17 months after the plantation, resulted in 501.5 g of dry matter/ plant. Also was accomplished the phytochemical evaluation and comparison of the secondary metabolites of the two species, in the Laboratório de Fitoquímica da Faculdade de Farmácia of the UFPR, using the hidroalcoholic and aqueous extracts obtained from stabilizes and triturated leaves and branchesform plants collected in the Fazenda Experimental do Canguiri of the UFPR. They were tested hidroalcoholic extract: sensorial caracteristics, % dry extract, alkaloids, coumarins, flavonoids, antraquinons, steroids/triterpenoids, aminogroups and luecoantocyantocyanindins; in aqueous extract: sensorial caracteristics, % dry extract, tannins, cyanigenic glycosids, saponins, anthocinains fixed and volatile acids and aminogroups. M. glomerata presented positive results for: coumarins, steroids/ triterpenoids, saponins and volatile acids; dark green color, sweetened aromatic scent, bitter flavour, pH 6,5n and dry residue if 14,85% for the hidroalcoholic extract and dark brown color, sweetened herbaceous scent, bitter flavour, pH 5,0 and dry residue of 8,93% for the aqueous extract. M. laevigata presented positive results for coumarins, steroids/triterpenoids, aminogroups, tannins ans saponins; dark green color, sweetened aromatic scent, bitter flavour, pH 6,0 and dry residue if 6,94% for the hidroalcoholic extract and dark brown color, sweetened herbaceous scent, bitter flavour, pH 5,5 and dry residue of 11,61% for the aqueous extract. For both species the results, in general, coincide with that in the literature. Based in the studies, it was concluded that: it is possible the use of M. laevigata as succedaneous of M. glomerata; in the propagation through guaco cuttings, is recommended the leaf area of 100 cm2 and the use of the carbonized rice seed coat, under manual irrigation, as substratum; there was no influence of the time of immersion of the base of the cutting in water; M. glomerata presented smaller tolerance to the cold than M. laevigata, wich presented the production of 501,5 g of dry matter/ plant.